IC 9470 - Analysis of Mine Fires for All US Underground and Surface Coal Mining Categories 1990-1999 - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
This report analyzes mine fires for all U.S. underground and surface coal mining categories by state and 2-year time periods during 1990-1999. Risk rate values are derived, and ignition source, methods of fire detection and suppression, and other variables are examined. The data were derived from Mine Safety and Health Administration (MSHA) mine fire accident publications and verbal communications with mine personnel. The analysis will provide the National Institute for Occupational Safety and Health, MSHA, and the mining industry with a better understanding of the causes and hazards associated with mine fires and will form a basis for future fire research programs.